THE YEARBOOK ON INTERNATIONAL ARBITRATION (VOLS. I–III) - N. Bocharova (BRICS Law Journal, 2016)
Reviewed book: 1–3 Yearbook on International Arbitration (Marianne Roth & Michael Geistlinger, eds.) (Intersentia 2010, 2012, 2013).